Sams teach yourself iOS 8 application development in 24 hours. - Ray, John, 1971-; Safari eBooks ([Place of publication not identified] : Sams, 2015)
"iOS 8 Video How-To is a series of short, 2- to 5-minute how-to videos that walk you through a specific task or technique related to iOS 8 application development. Adapted from John Ray's book Sams Teach Yourself iOS 8 Application Development in 24 Hours, each video is self-contained and focused entirely on one particular task. You can either go through the videos in sequence or you can jump into a particular task, see how something is done, and then jump out again."--Resource description page.
Title from title screen (viewed January 19, 2016).
Presenter, John Ray.
Date of publication from resource description page.
"Video 1.1."
Keywords: iOS (Electronic resource); Application software -- Development; Electronic books